Japanese Reverse Compasses: Grounding Cognition in History and Society. Issue 2 (31st May 2018) - Frumer, Yulia
Argument: An unusual compass, on which east and west are reversed, provides insight into the dynamics guiding our understanding of artifacts. By examining how such compasses were used in Tokugawa Japan (1600–1868), the benefits they brought, and how users knew how to read them, this article uncovers the cognitive factors that shape our interaction with technology. Building on the methodological approach of the distributed cognition theory, the article claims that reverse compasses allowed the user to conserve cognitive effort, which was particularly advantageous to Tokugawa-period mariners. Moreover, the article shows that even non-professional Tokugawa Japanese had a relatively easy time reading reverse compasses due to similarity between the compasses' orientation and Tokugawa timekeeping practices. Building on the bodily and cognitive habits they had developed through the practices of keeping time, users could identify and interpret cultural cues embedded in the structure of reverse compasses.